The Effect of Financial Literacy, Income, And Financial Planning on Stock Investment Decisions - Nanda Prastiwi, Bellia; Utami, Helianti; Juliardi, Dodik (Lafadz Jaya Publisher, 2023)
This study examines the effect of financial literacy, income, and financial planning on stock investment decisions. The population in this study uses young workers who are members of the Beginner Stock Investor (ISP) community. This study used a questionnaire distributed to members of the ISP community in East Java as a sample, with 100 respondents. Sampling using non-probability sampling with a purposive sampling approach. This study uses descriptive and multiple linear regression analysis to test the hypothesis. From the multiple linear regression analysis results, the researchers found that financial literacy, income, and financial planning affect stock investment decisions.